“We and the nurses are now working with one voice”: How community leaders and health committee members describe their role in Sierra Leone’s Ebola response - McMahon-Rössle, Shannon A. (BMC health services research, 2017)
Across low-income settings, community volunteers and health committee members support the formal health system - both routinely and amid emergencies - by engaging in health services such as referrals and health education. During the 2014-2015 Ebola epidemic, emerging reports suggest that community engagement was instrumental in interrupting transmission. Nevertheless, literature regarding community volunteers’ roles during emergencies generally, and Ebola specifically, is scarce. This research outlines what this cadre of the workforce did, how they coped, and the facilitators and barriers they faced to providing care in Sierra Leone.
Gesehen am 20.11.2018